Prevalence and characterization of ciprofloxacin-resistant Salmonella enterica spp. isolated from food animals during 2010–2023 in South Korea - Md. Sekendar Ali; Hee-Seung Kang; Bo-Youn Moon; Ye-Eun Heo; Min Young Kim; Ji-Hyun Choi; Yu-Jeong Hwang; Ji-In Kim; Yeon-Hee Lee; Jae-Myung Kim; Suk-Kyung Lim (Veterinary Quarterly)
We isolated 6,561 Salmonella strains from food animals, cattle (n = 217), pigs (n = 1526), chickens (n = 3942), and ducks (n = 876). Isolates were evaluated for antimicrobial sensitivity, mutations in quinolone resistance determination regions (QRDRs), and plasmid-mediated quinolone resistance (PMQR) genes. Clonal relationship and genetic diversity were assessed by multi-locus sequence typing (MLST) and pulsed-field gel electrophoresis (PFGE). Overall, 3.1% of isolates exhibited resistance to ciprofloxacin. Commonly identified mutations in QRDRs were S83F, D87N, and D87G in gyrA; T57S and S80I in parC; and L416F in parE. Furthermore, mutations differed by serotypes. In S. Albany, S83F mutation in gyrA and T57S in parC were prevalent, while in S. Kentucky, S83F and D87N in gyrA, T57S and S80I in parC; and in S. Indiana, S83F and D87G in gyrA, T57S and S80R in parC, and L416F in parE were common. Amongst PMQRs, qnrS was mainly observed in S. Albany, aac(6′)-Ib-cr in S. Indiana, and qnrB1 in S. Albany. Among STs, ST198 S. Kentucky was predominant, followed by ST292 S. Albany and ST17 S. Indiana. Of 26 pulsotypes, KX1KA1 was mainly identified in S. Kentucky, AX1AA1 in S. Albany, and IX1IA1 in S. Indiana. Taken together, ciprofloxacin-resistant Salmonella can pose health hazards to humans and other animals.